Socio-political attitudes 1975 - Ekehammar, Bo (Stockholm University, 2026)
The central aim of the study is looking at various aspects of political perception as a function of socio-political ideology. The politically percepted objects consists mainly of political parties, party-leaders and countries. The measurement of political perception is made through multi-dimensional scaling, semantic differential and political differential. Political ideology is operationalized through party affiliation and socio-political attitude (measured with a specially designed scale). From these data some indexes are generated on the individual level for cognitive articulation and cognitive differentiation which then are related to the individual's socio-political ideology. The first part of the study contains questions about attitudes to various phenomena in society, socio-economical questions, party preferences (own, parents), education of relatives, estimation of: left-right, religiosity and extremism. The second part (where the sample is a subgroup of the first part's sample) contains the same questions plus estimations of: some Swedish politicians, countries (Sweden, USA, the Soviet Union and China) and Swedish political parties.

Det centrala syftet med studien är att undersöka olika aspekter av politisk perception som en funktion av sociopolitisk ideologi. De politiskt uppfattade objekten består huvudsakligen av politiska partier, partiledare och länder. Mätningen av politisk perception görs genom multidimensionell skalning, semantisk differential och politisk differential.
Politisk ideologi operationaliseras genom partitillhörighet och sociopolitiska attityder (mätta med en särskilt utformad skala). Utifrån dessa data genereras vissa index på individnivå för kognitiv artikulation och kognitiv differentiering, vilka sedan relateras till individens sociopolitiska ideologi.
Den första delen av studien innehåller frågor om attityder till olika fenomen i samhället, socioekonomiska frågor, partipreferenser (egna och föräldrars), anhörigas utbildning samt skattningar av vänster–höger-position, religiositet och extremism.
Den andra delen (där urvalet utgörs av en delgrupp av den första delens urval) innehåller samma frågor samt dessutom skattningar av vissa svenska politiker, länder (Sverige, USA, Sovjetunionen och Kina) samt svenska politiska partier.
Sociopolitiska attityder 1975
Keywords: Political behaviour and attitudes; Politiska beteenden och attityder; Youth; Ungdomar; Social behaviour and attitudes; Socialt beteende och attityder; Social Sciences; Samhällsvetenskap